“THE ROLE OF EDUCATION IN BUILDING A BETTER FUTURE” (Ilm fan taraqqiyotida raqamli iqtisodiyot va zamonaviy ta'limning o'rni hamda rivojlanish omillari, 2025)
Abstract: Education develops society. If a person does not illuminate his path with the light of knowledge, he will remain on the street of darkness and ignorance. The light of the human soul is strengthened by knowledge and enlightenment. Knowledge creates the dignity of humanity. No one has ever been harmed by science. Acquiring knowledge is an art.